Development of a protein nanoparticle platform for targeting EGFR expressing cancer cells - Buecheler, Jakob W. (2015)
BACKGROUND: A range of protein-based nanoparticles has been developed for cancer drug delivery and diagnostics. This includes the E2 protein derived from the pyruvate dehydrogenase complex in Geobacillus stearothermophilus which assembles into a 60-subunit protein cage structure that is capable of encapsulating cancer therapeutics. In this study antibody fragments targeting the epidermal growth factor receptor (EGFR) were tethered to the surface of E2 protein nanoparticles to determine whether the protein nanoparticles could be speciﬁcally targeted to EGFR overexpressing cancer cells. RESULTS: Variants of the anti-EGFR antibody fragment and the E2 protein containing speciﬁc cysteine residues (E2ΔN17A186C) were conjugated using a maleimide-speciﬁc crosslinker. Electron microscopy and dynamic light scattering analysis indicated that the cysteine modiﬁed E2 protein correctly assembled into a 25–30 nm particle. The conjugation of the anti-EGFR antibody fragment (26 kDa) with a subunit of the E2 protein (26 kDa) was conﬁrmed by mass spectrometry with an estimated molecular weight of 52 kDa. The binding of the conjugated E2 particle to native EGFR on MDA MB 231 cells and recombinant EGFR was conﬁrmed using ﬂow cytometry and biolayer interferometry, respectively. CONCLUSIONS: In this study, proof-of-principle that an EGFR-targeting scFv can be stably conjugated to the cysteine variant E2ΔN17A186C protein nanoparticle without loss of targeting capability has been demonstrated. Conceptually scFv antibody fragments reactive with other important cancer targets could be utilized and presents the opportunity for generation of multi-targeted protein nanoparticles by conjugating various scFvs with diﬀerent speciﬁcities on the same particle.